Development of Pan Obibul (Papan Operasi Bilangan Bulat) Media to Improve Mathematic Higher Order Thinking Skills of Elementary Students in Problem Based Learning Model (Universitas Negeri Semarang, 2022)
Mastery of mathematical concepts is still an obstacle for elementary school students. They still consider mathematics as an abstract concept, so it is necessary to provide learning media that can help students to master the concept well. Problem solving based media is believed to be able to help students to practice higher order thinking skills (HOTs). Therefore, Pan Obibul media was developed to train higher order thinking skills which at the same time had an impact on mastering mathematical concepts. This research aims to determine the validity, practicality, and effectiveness of the Pan Obibul learning media that is implemented with the Problem Based Learning model on students' HOTS abilities. The type of research is R & D, and the research data were obtained through interviews, teacher and student needs questionnaires, validator questionnaires, teacher, and student response questionnaires, as well as pretest and posttest. The research was conducted at a public school in Wedarijaksa district, Pati Regency with a total of five schools. The results showed that the feasibility assessment by lesson material validators obtained an average percentage of 94.55% which is included in the very suitable category. The responses of teachers and students to the Pan Obibul media product trial obtained an average percentage of 85.25% and 87.5% with a very suitable category. The the mathematics HOTS abilities improvement can be known by the paired sample test and N-Gain test.In paired sample t-test, it was obtained that an average Sig (2-tailed) score 0.000 and included in effective category. The results of the N-gain test obtained the value of 0.606 and included in the high category. From those results, it can be concluded that the development of Pan Obibul media to improve the HOTS skill of elementary school students through the PBL learning approach obtained Pan Obibul media, which is valid, practical, and effective in learning mathematics.